Green ear yield potential of tropical field maize at two levels of nitrogen fertiliser application in Ibadan, Nigeria (2015)
Green maize plays a significant role in the social and economic life of the peoples of the humid forest and derived savannah agro-ecologies of West and Central Africa. Appropriate strategies for its production would contribute significantly to sustainable agriculture. Fourteen tropical field maize genotypes, consisting of hybrids and open pollinated varieties (OPVs), were evaluated in field trials for green ear yield at two levels (30 and 60 kg ha-1) of nitrogen fertilizer application during the main cropping seasons of 2012 and 2013. A factorial in a split plot design with three replications was used. Fertilizer levels were main plots and maize genotypes subplots. Highly significant genotype, N level and genotype × N level effects were observed for all traits considered. The range in yield of marketable cobs at 30 kg N ha-1 and 60 kg N ha-1 were 98.4% and 108.6% of the respective means. The number and yield of ears, yield of cobs and number and yield of marketable cobs were significantly reduced at 30 kg N ha-1. The percentage reduction in yield of marketable cobs was 55.9%. Yield of marketable cobs and other measured green ear yield variables at 30 kg N ha-1 for OPVs were significantly higher than for the hybrids, while the differences were not significant at 60 kg N ha-1. Suwan-1 STR produced the highest number and yield of marketable cobs per hectare both at 60 kg N ha-1 and across N levels. At 30 kg N ha-1, the top yielding genotypes were ACR97 TZL COMP1 C2 (2.82 t ha-1), TZE COMP3 C2 (2.71 t ha-1) and 9044-27 STR (2.51 t ha-1), while the best three genotypes at 60 kg N ha-1 were Suwan-1 (6.56 t ha-1), AK96DMR-L-SR-W (5.91 t ha-1) and 9144-4 (5.28 t ha-1). Yield of marketable cobs in this study at 30 and 60 kg N ha-1 was 46.5 and 49.1% of the yield of ears ha-1, respectively. Genetic variation for green ear yield was present among the maize genotypes studied and this was greatly influenced by the level of N fertiliser application.